2009
DOI: 10.1097/mcg.0b013e3181862a8c
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Alone Versus Propofol in Combination With Meperidine for Sedation During Colonoscopy

Abstract: For sedated colonoscopy, propofol in combination with meperidine is better than propofol alone in improving patients' tolerance and recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 31 publications
2
39
1
5
Order By: Relevance
“…[22] On the other hand, Lopez et al [30] found a lower rate of hypoxemia when propofol was used alone compared with propofol-meperidine during gastroscopy. Their observed incidence of hypoxemia in propofol-meperidine group (11.9%) was comparable to our findings (9.1%).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[22] On the other hand, Lopez et al [30] found a lower rate of hypoxemia when propofol was used alone compared with propofol-meperidine during gastroscopy. Their observed incidence of hypoxemia in propofol-meperidine group (11.9%) was comparable to our findings (9.1%).…”
Section: Discussionmentioning
confidence: 99%
“…[22,23-25-28] It has been shown that the addition of ketamine to propofol allowed stable hemodynamics because of sympathomimetic effects of ketamine and reduced risk of hypoxemia even in pediatric patients with cardiac defects during procedural sedations. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]24] In a prospective randomized study by Nejati et al [25] , it was reported that hypotension and hypoxemia was not observed in two of 31 patients (6.45%) and apnea was observed in one of 31 patients (3.2%) during sedation for colonoscopy with a 1:1 mixture of ketamine and propofol. Tosun et al [12] found similar rate of hypoxemia (6.52%) and no hypotension with ketamine and propofol sedation in pediatric patients who underwent UGE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations